Menjadi Guru Kreatif melalui Aplikasi Canva - Syam Tonra, Wilda; Angkotasan, Nurma; Prawitha Sari, Diah; Ikhsan, Muhammad (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
The results of observations and interviews with teachers and principals at SD Islamiyah 6 Ternate City in early 2022 found several problems in the learning process (a) Teachers have not been creative in implementing learning, especially the use of technology (b) Teacher competence in utilizing media in learning is still needs to be improved (c) there is no good integration of each subject with blended-based learning media during the covid-19 pandemic. Therefore, there is a great need for training on the use of Canva for teachers. The purpose of implementing this community service (PKM) is to provide insight and creativity to teachers through Canva so that they can improve the abilities and competencies in providing interesting media in classroom learning. The participants are the 10 teachers at SD Islamiyah 6 City of Ternate. The training method are presentation and discussion. Then demonstration and practical training. The result obtained in this activity is an increase in teacher competence through Canva. This can be seen from the results of the teacher's own design on teachers’ device/handphone respectively. After the training, the teachers gave an assessment of the respondent's questionnaire in the implementation of this PKM activity with a very good category.